SOCIOLOGICAL KNOWLEDGE IN THE CONCEPT OF CONFLICT TRANSFORMATION J. P. LEDARACA - Сорока, Ю. Г. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2021)
The spread of dialogue and conflict transformation practices in modern Ukraine creates a demand for academic, in particular sociological support of such processes. It becomes one of the tools to support relevant projects through sociological reflection of its goals and objectives, implemented practices, activities and consciousness of project participants and its audience. At present, such sociological support exists without a formed methodological basis, one of the areas of creation of which is the study of common principles of building peace and social sciences, in particular sociology. The article considers the use of sociological knowledge in the concept of conflict transformation by J.P. Lederach, in particular, his use of the concepts of identity, power, divided societies, conflict dynamics, social relations, social changes and more.In the perspective of sociological reading, building peace is seen as a process of social change, the signal of which is the need for conflict and confrontation within society, which can not be resolved in the perspective of the state approach, require a systematic vision of existing social relations and constructive intervention, finding opportunities for dialogue.The selection of sociological concepts and practices as components of the concept of peace building by J.P. Lederach contributes to the understanding of it as an interdisciplinary field of research and activity. The presented analysis demonstrates the potential of involving various academic disciplinary approaches in solving building peace tasks. In addition to conflict studies, political science, law, it can also be researched by social and historical memory studies, ethnopsychological and ethnosociological research, regional and cultural research, and so on. The academic field thus reveals its own potential for supporting peace-building processes.